The Impact Of Electronic Word-of-Mouth Marketing (Ewom) Acceptance On Purchase Intentions For Household Products On TikTok Shop - Nguyen Thi Phuong, Giang; Ngo Thi Thanh, Huong; Tran Thi Huynh , Nhu; Thai Dong, Tan (Journal of Economics and Administrative Sciences, 2025)
This article aims to discover the influence of Electronic word of mouth (eWOM) on consumer purchase intentions within the context of TikTok Shop, with particular attention given to household products. The motivation behind this study is to explain key variables that determine the role of eWOM as a major driver of consumer behavior in the digital market. A detailed model was also recommended to clearly establish how information perceived as useful and reader attitudes towards shared content influence purchasing behaviors. Conducting a mixed-methods investigation, this study aims at collecting the necessary data on 500 consumers from Ho Chi Minh City, then analyzing it via SPSS 24 and SmartPLS 4. The findings indicate the mediating effect of the acceptance of eWOM, its high impact on purchase intentions, as well as its relation to a great many other variables. These discoveries could guide some corporate strategies aimed at enhancing eWOM for maximum customer engagement on the worldwide stage for competitive marketing.